Scale-invariance of ruggedness measures in fractal fitness landscapes. Issue 5 (3rd September 2018) - Richter, Hendrik
Graphical Abstract: Fractal fitness landscape of the targeting problem. Abstract : The paper deals with using chaos to direct trajectories to targets and analyses ruggedness and fractality of the resulting fitness landscapes. The targeting problem is formulated as a dynamic fitness landscape and four different chaotic maps generating such a landscape are studied. By using a computational approach, we analyse properties of the landscapes and quantify their fractal and rugged characteristics. In particular, it is shown that ruggedness measures such as correlation length and information content are scale-invariant and self-similar.